ATU-08 Genetic studies of MRI liver fat content identify susceptibility variants with variable metabolic effects. (June 2019) - Parisinos, Constantinos; Wilman, Henry; Kelly, Matt; Neubauer, Stefan; Thomas, Louise; Bell, Jimmy; Hingorani, Aroon; Patel, Riyaz; Hemingway, Harry; Banerjee, Rajarshi; Yaghootkar, Hanieh
Abstract : Background and aims: Excess liver fat affects up to 1 in 4 adults globally 1 and has been implicated in the pathogenesis of liver disease including cirrhosis and hepatocellular carcinoma, as well as extrahepatic diseases such as type 2 diabetes and cardiovascular diseases 2 . We aimed to find genetic variants influencing liver fat content. Methods: Data was acquired from UK Biobank (application 9914). Liver phenotypes were calculated from MRI data by trained analysts using LiverMultiScanTM. We used GEMMA to perform a genome-wide association study (GWAS) of MRI scan measures of liver fat using 8, 289 individuals of European ancestry from UK Biobank. We adjusted our analysis for age, sex, BMI, genotyping array, and population structure. Results: We identified two loci in/near PNPLA3 ( rs738409, p = 2.1 x 10 −41 ) and TM6SF2 (rs58542926, p = 4.3 x 10 −40 ) that reached genome-wide significance. We further identified four suggestive loci previously associated with circulating lipid levels, type 2 diabetes and obesity ( APOE, GPAM, TRIB1, GCKR). Phenome-wide association analysis (PheWAS) of rs58542926 in TM6SF2 demonstrated positive associations with diabetes, rosacea and liver cirrhosis, and inverse associations with cholesterol, peripheral vascular disease, gout, pulmonary embolism and gallstones. Phenome-wide association analysis of rs738409 in PNPLA3 demonstrated positive associations with liver disease, type 2 diabetes and hypertension, and inverse associations with height, hip circumference, leg and arm fat free mass, cholesterol, and ischaemic heart diseases. Conclusion: This is the first GWAS using MRI determined liver fat content to date. Mechanisms underlying elevated liver fat content contribute to hypertension and type 2 diabetes risk, but may also confer health benefits. The identification of loci previously associated with non-alcoholic fatty liver disease provide genetic validation of the utility of MRI for a fast and non-invasive assessment of liver fat content. References: Younossi, Z et al. Global burden of NAFLD and NASH: trends, predictions, risk factors and prevention. Nat. Rev. Gastroenterol. Hepatol. 15, 11–20 (2018). Adams, L A, Anstee, Q M, Tilg, H. & Targher, G. Non-alcoholic fatty liver disease and its relationship with cardiovascular disease and other extrahepatic diseases. Gut (2017). doi:10.1136/gutjnl-2017–313884